RI 2692 The Physical Chemistry Of Oil-Field Emulsions. - D. B. Dow (The National Institute for Occupational Safety and Health (NIOSH), 1925)
This paper on the physical chemistry of oil-field emulsions is the last of a series of three prepared as a result of a study of oil-field emulsions. The first paper3 deals with the factors responsible for the formation of emulsions, find the second4 with methods now utilized for dehydrating oil-field emulsions. A more complete report of the whole investigation is in preparation. The laws governing the formation and resolution of oil-field emulsions fall in that branch of physical chemistry doling with colloids. Much work has been done by the physical chemist on colloids And emulsions, and, although most of this work was on commercial and pharmaceutical emulsions, yet the principles developed apply in a general gray to oil-field emulsions.